Training Effectiveness of Skill Development Training Programmes among the Aspirational Districts of Karnataka - Kumar, G. S. Arun; Nain, M. S.; Singh, Rashmi; Kumbhare, N. V.; Parsad, Rajender; Kumar, Shiv (Indian Journal of Extension Education, 2021)
Aspirational districts programme was launched by GOI in 2018 to raise the living standards of citizens by focusing on five major thematical areas viz. health and nutrition, education, agriculture and water resources, financial inclusion and skill development and basic infrastructure in the poor performing 115 districts of the country. The problem of unemployment and poverty in rural areas can be tackled by inculcating the desirable skills and develops entrepreneurial ability. The study was focused on assessing the effectiveness of skill development training programmes in two aspirational districts (Raichur and Yadgir) of Karnataka. Primary data was collected from 120 trainees including 30 farmers and 30 agricultural labours from each district trained under various skill training institutes. The independent variables like number of training programmes attended, learning motivation, innovativeness, motivation to transfer learning, self-efficacy and achievement motivation were positive and significantly affecting the training effectiveness. The overall effectiveness of training was found to be 51 per cent which came under medium effectiveness category. Among the different aspects of training programme ‘coverage’ was found to be more effective. But trainings were least effective in ‘need assessment’ of trainees. A majority of trainees perceived that training improved their knowledge and skills.
Keywords: Aspirational district programme; Training effectiveness; Skill development; Perceived benefits